Application of cluster management in COVID-19 prevention and control in the Emergency Department of a certain hospital of Traditional Chinese Medicine (新型冠状病毒肺炎疫情防控期间中医院急诊科集束化管理措施) - LIU Ai (刘爱); FENG Ying (冯莹); TONG Lu (佟璐); ZUO Ling (左琳); ZHAO Lina (赵丽娜); LI Yue (李悦); YAN Hong (颜红) (中西医结合护理)
The emergency department, as an important gateway of epidemic prevention and control in the hospital, bears the responsibility of prevention and control of COVID-19. Hospital highlighted the role of the emergency department in prevention and control of COVID-19. Based on relevant rules and regulations and guidelines of COVID-19 prevention and control, a continuous strategy of prevention and control was implemented according to the actual situation and characteristics of the emergency department. Great efforts were made to enhance the COVID-19 prevention and control, and cluster management measures were carried out including reforming the diagnosis and treatment environment, formulating principals and process of prevention, pre-screening, personnel training, cleaning and disinfection, and supervision of prevention and control. (急诊科作为医院防控疫情的重要关口, 担负着重要的防控职责。本院急诊科高度重视新型冠状病毒肺炎疫情防控工作, 依据国家相关制度及防治指南, 结合医院疫情防控工作实际和急诊科特点, 始终落实预防为主的方针, 加强防控管理, 制订了急诊科集束化管理措施, 包括改造诊疗环境、防控制度和流程的制定、预检筛查、人员培训、清洁消毒、防控督导等。)